The Phenomenon of Responsibility in the Russian and English Languages and its Applied Relevance - M., Akpayeva A.; B., Shakenova V. (Farabi Journal of Social Sciences, 2019)
Abstract. The key role of individual’s responsibility determination in the Russian language is in world predictability or, vice versa, unpredictability. Although in English, the responsibility is likely born by an individual rather than by external factors. In this presentation, mostly we deal with the responsibility of individual persons. Moreover, basing on the definition of the word in two languages we can see that there is a divergence in understanding responsibility.